2018
DOI: 10.4081/xeno.2018.7674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure to benzophenone and diclofenac on DNA methylation levels and reproductive success in a marine copepod

Abstract: The UV-filter benzophenone and the anti-inflammatory diclofenac are commonly detected in the environment. The aim of this study was to assess the multigenerational effects of chronic exposure to low concentrations of these chemicals on toxicity and DNA methylation levels in the copepod Gladioferens pectinatus. Acute toxicity tests were conducted to determine the sensitivity of G. pectinatus to the chemicals. All chemicals impacted breeding, hatching and egg viability. Diclofenac (1 mg.L-1) reduced the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…There are few ecotoxicological studies regarding benzophenone. A marine copepod chronically exposed to benzophenone exhibited decreased egg viability and hatching success as well as significant genomic DNA methylation, raising concerns for potential intra- and trans-generational evolutionary effects. In rainbow trout, benzophenone binds to the trout estrogen receptor and induces vitellogenin mRNA in liver slices . A more fascinating historical examination of benzophenone is that the first patents on benzophenone were for its herbicidal properties.…”
Section: Discussionmentioning
confidence: 99%
“…There are few ecotoxicological studies regarding benzophenone. A marine copepod chronically exposed to benzophenone exhibited decreased egg viability and hatching success as well as significant genomic DNA methylation, raising concerns for potential intra- and trans-generational evolutionary effects. In rainbow trout, benzophenone binds to the trout estrogen receptor and induces vitellogenin mRNA in liver slices . A more fascinating historical examination of benzophenone is that the first patents on benzophenone were for its herbicidal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis revealed the nylon microplastics used in these exposures contain compounds that may cause toxicity or endocrine disruptionalthough it should be noted this analysis does not tell us which compounds, nor how much, could be expected to leach from the nylon either in seawater or the intestinal tract of a copepod. For example, the UV-stabilizer benzophenone, identified in the nylon fibers, has been shown to increase DNA methylation and significantly reduce egg hatching success in the marine copepod Gladioferens pectinatus , and act as an oestradiol agonist in rats and fish. , It is crucial to recognize that plastics are not an inert material, but a complex mixture of polymers containing a wide spectrum of compounds that have the potential to leach out . Given the capacity for these compounds to cause endocrine disruption or toxicity, it is crucial that chemical profiling of microplastics used in toxicity testing becomes more commonplace.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental risks of diclofenac have been investigated, and the results showed that diclofenac and its metabolites can cause a high risk due to the synergistic interactions with other pollutants, the creation of new drug-resistant strains, and the generation of novel emerging contaminants (Sathishkumar et al 2020 ). Chronic effects of diclofenac are reported on DNA methylation level and reproductive ability in Gladioferens pectinatus (marine copepod) (Guyon et al 2018 ). Diclofenac contaminants can lead to DNA damage, oxidative stress, the raised activity of cyclooxygenase, and diminished stability of the lysosomal membrane in the mussel Perna perna (Fontes et al 2018 ).…”
Section: Pharmaceuticalsmentioning
confidence: 99%